The Combination of Oral PDE5-Inhibitor (Sildenafil) And Oral Prostacyclin Analogue (Beraphrost) Therapy for Increasing Quality of Life in Adults with Pulmonary Arterial Hypertension Related to Uncorrected Secundum Atrial Septal Defect - Heny Martini; Muhammad Rizki Fadlan; Akhmad Isna Nurudinulloh (Universitas Brawijaya, 2021)
Background : Sildenafil, an oral phosphodiesterase type-5 inhibitor, has vasodilatory effects through a cyclic guanosine 3,5-monophosphate–dependent mechanism, whereas beraprost, an oral prostacyclin analog, induces vasorelaxation through a cAMP-dependent mechanism.Objective : To investigate whether the combination of oral sildenafil and beraprost is superior to sildenafil alone in in adult patients with PAH related uncorrected secundum ASD.Method : Patients with secundum ASD who developed PAH divided into two group. Group A received oral sildenafil 3x40 mg and oral beraphrost 3x20mcg. Group B received oral sildenafil only 3x40 mg in a 12-week. Health-related quality of life (HRQoL) was recorded by patients using the Medical Outcomes Study 36-item short form (SF-36) questionnaires at baseline and after 12 of therapy. Therapy adherence was achieved through a series of phone calls and a four-weekly hospital visit. Every normal follow-up appointment included an examination of side effects and a dosage modification based on the clinical situation.Results : We didn’t found any significant of proportion different in Comorbid condition between groups. Compared with Group B, Group A had increased in physical functioning, Limitation to physical health, Energy fatigue, Pain, and health change (P=0.00, P=0.03, P=0.044, P=0.026, P=0.008, respectively).Conclusion : We suggest that combination between oral sildenafil therapy 40 mg three times per day and Beraphrost 20mcg two times per day significantly increase the HRQOL in PAH patients due to uncorrected secundum ASD.